ประสิทธิผลการเช็ดตัวด้วยยาเขียวหอมกับการเช็ดตัวลดไข้ รูปแบบเดิมต่อการลดอุณหภูมิร่างกายในผู้ป่วยที่มีไข้: Effectiveness of Wiping with Khiao Hom Medicine and Traditional Antipyretic Wiping in Reducing Body Temperature in Patients with Fever. - Jamchun Werathep,กรรณิการ์ (วารสารวิชาการกรมสนับสนุนบริการสุขภาพ, 2025)
การศึกษาครั้งนี้ เป็นการวิจัยกึ่งทดลองแบบสองกลุ่มวัดผลก่อนหลัง (Quasi-experiment Two group pre-post test) มีวัตถุประสงค์เพื่อเปรียบเทียบประสิทธิผลต่อการลดอุณหภูมิร่างกาย และความพึงพอใจของการเช็ดตัวลดไข้ด้วยยาเขียวหอมกับการเช็ดตัวแบบเดิมของผู้ป่วยที่มีไข้ ณ แผนกผู้ป่วยใน โรงพยาบาลเสาไห้เฉลิมพระเกียรติ ๘๐ พรรษา ระหว่างวันที่ 1 มีนาคม 2568 ถึง 30 มิถุนายน 2568 ค????ำนวณตัวอย่างโดยใช้สูตรการเปรียบเทียบค่าเฉลี่ยของสองกลุ่มอิสระ (Two Independent Means) ได้กลุ่มตัวอย่าง 50 คน แบ่งเป็น 2 กลุ่ม กลุ่มละ 25 คน เก็บข้อมูลโดยแบบเก็บข้อมูล แบ่งเป็น 3 ส่วน คือ ส่วนที่ 1 ข้อมูลส่วนบุคคล ประกอบด้วย เพศ อายุ น้ำหนัก ส่วนสูง ค่าดัชนีมวลกาย ส่วนที่ 2 อุณหภูมิก่อนเช็ดตัว และหลังเช็ดตัวที่เวลา 30, 60, 90 และ 120 นาที และส่วนที่ 3 ความพึงพอใจต่อวิธีการเช็ดตัว ผลการวิจัยพบว่า กลุ่มที่ได้รับการเช็ดตัวด้วยยาเขียวหอมมีประสิทธิผลในการลดอุณหภูมิร่างกายสูงกว่าวิธีการเช็ดตัวแบบเดิมอย่างมีนัยสำคัญ ตั้งแต่ 30 นาทีหลังเช็ดตัว (p = 0.038) และพบความแตกต่าง ชัดเจนยิ่งขึ้นที่เวลา 60, 90 และ 120 นาที (p < 0.001) ด้านข้อมูลพื้นฐานพบว่า ค่าเฉลี่ยดัชนีมวลกายของกลุ่มเช็ดตัวด้วยยาเขียวหอมต่ำกว่ากลุ่มเช็ดตัวด้วยวิธีเดิมอย่างมีนัยสำคัญ (p = 0.005) ขณะที่เพศ ส่วนสูง และน้ำหนักไม่แตกต่างกัน ด้านความพึงพอใจ กลุ่มเช็ดตัวด้วยยาเขียวหอมมีคะแนนสูงกว่าการเช็ดตัวแบบเดิมทุกด้าน สรุปได้ว่า การเช็ดตัวด้วยยาเขียวหอมเป็นวิธีลดไข้ที่มีประสิทธิผลมากกว่าการเช็ดตัวลดไข้แบบเดิม ทั้งการลดอุณหภูมิของร่างกายได้รวดเร็วและการทำให้ผู้ป่วยรู้สึกสบายตัวมากขึ้น จึงสามารถนำมาเป็นแนวทางการพยาบาลทางเลือกและสนับสนุนการใช้สมุนไพรไทยในการดูแลผู้ป่วยที่มีไข้ในสถานพยาบาลได้อย่างเหมาะสม ข้อเสนอแนะ ควรศึกษาในกลุ่มที่มีช่วงอายุและดัชนีมวลกายใกล้เคียงกันเพื่อลดอคติ และส่งเสริมการใช้ยาเขียวหอมเป็นทางเลือกเมื่อไม่สามารถใช้ยาลดไข้ได้ พร้อมทั้งอบรมผู้ดูแลเกี่ยวกับการใช้สมุนไพรอย่างถูกต้องเพื่อเพิ่มประสิทธิผล This quasi-experimental study, a two-group pre-post test, aimed to compare the effectiveness of green herbal compresses on reducing body temperature and satisfaction with traditional compresses for fever in patients at the inpatient department of Saohai Chaloem Phrakiat 80th Birthday Anniversary Hospital between March 1, 2025, and June 30, 2025. The sample was calculated using the Two Independent Means formula. Fifty subjects were divided into two groups of 25 subjects each. Data were collected using a data collection form divided into three parts: Part 1: Personal data, including gender, age, weight, height, and body mass index; Part 2: Body temperature before and after compresses at 30, 60, 90, and 120 minutes; and Part 3: Satisfaction with the compresses method. The results showed that the group receiving the green herbal compresses Onion was significantly more effective in reducing body temperature than the traditional body wiping method as early as 30 minutes after wiping (p = 0.038), and the difference was more pronounced at 60, 90, and 120 minutes (p < 0.001). In terms of baseline data, the body mass index (BMI) of the green onion wiping group was significantly lower than the conventional wiping group (p = 0.005). However, there was no difference in gender, height, and weight. In terms of satisfaction, the green onion group scored higher than the conventional method in all dimensions. In conclusion, green onion wiping is a more effective fever-reducing method than the conventional wiping method, both in terms of reducing body temperature quickly and making patients feel more comfortable. Therefore, it can be used as an alternative nursing guideline and to support the appropriate use of Thai herbs in the care of patients with fever in hospitals. Recommendations should be studied in groups with similar age ranges and BMIs to reduce bias and promote the use of green onion as an alternative when antipyretic drugs are unavailable. Caregivers should be trained on the correct use of herbs to increase effectiveness.